Asymmetric Addition to Ketones: Enantioselective Formation of Tertiary Alcohols - Garcia, Celina; Martin, Victor S. (Current Organic Chemistry, 2006)
The stereoselective formation of chiral tertiary alcohols is of great importance for the synthesis of enantiomerically pure natural products and pharmaceuticals. The simplest approach for the preparation of chiral alcohols is the enantioselective addition of organometallic reagents to carbonyl compounds. Hundreds of catalysts promote nucleophilic additions of organometallic compounds to aldehydes with high enantioselectivities. However, the use of ketones as group acceptors under similar conditions has proven much more challenging. The chemistry of catalytic asymmetric additions to ketones is progressing, especially since 1998. This review attempts to cover advances in this field which have occurred between 1994-2004. Particular attention is paid to chiral auxiliaries, reagents and catalysts used for the addition to different kinds of ketones (aromatic and aliphatic ketones, α, β-unsaturated ketones, α-ketoesters) as well as the enantiomeric excesses of the chiral tertiary alcohols obtained for each case. In addition, a discussion about the progress in the catalytic asymmetric addition to ketoimines in order to generate enantiomerically enriched tertiary amines will be presented. Finally, recent applications of the asymmetric addition to ketones chemistry in the synthesis of natural products and related compounds are reported.
Keywords: camptothecin